'Smart' non-viral delivery systems for targeted delivery of RNAi to the lungs. (January 2013) - Ramsey, Joanne M; Hibbitts, Alan; Barlow, James; Kelly, Ciara; Sivadas, Neeraj; Cryan, Sally-Ann
The emergence of RNAi offers a potentially exciting new therapeutic paradigm for respiratory diseases. However, effective delivery remains a key requirement for their translation into the clinic and has been a major factor in the limited clinical success seen to date. Inhalation offers tissue-specific targeting of the RNAi to treat respiratory diseases and a diminished risk of off-target effects. In order to deliver RNAi directly to the respiratory tract via inhalation, 'smart' non-viral carriers are required to protect the RNAi during delivery/aerosolization and enhance cell-specific uptake to target cells. Here, we review the state-of-the-art in therapeutic aerosol bioengineering, and specifically non-viral siRNA delivery platforms, for delivery via inhalation. This includes developments in inhaler device engineering and particle engineering, including manufacturing methods and excipients used in therapeutic aerosol bioengineering that underpin the development of smart, cell type-specific delivery systems to target siRNA to respiratory epithelial cells and/or alveolar macrophages.